C.1 - "Eisenhower, Dwight D" (New York, 1961)
This book covers the following topics World peace- a balance sheet; Inaugural address 1953;Toward a golden age of peace; Peace begins with the individual; Art of peace; Propaganda and Truth; The ideal of Peace; The desire to be free; The hope of mankind; two great goals; Ancient dream of man; The force for peace; First steps toward Peace; Justice to all nations; The prayer by which we live; Seeking world security; Freedom is the destiny of man; A dedication of brotherhood; We must proceed by Faith; That man may walk unafraid; To resist aggression; A single rule of law; Under one banner; The American republics etc.